2010
DOI: 10.4081/or.2010.e6
|View full text |Cite
|
Sign up to set email alerts
|

Management of type II superior labrum anterior posterior lesions: a review of the literature

Abstract: Superior labrum anterior and posterior lesions were first described in 1985 by Andrews et al. and later classified into four types by Synder et al. The most prevalent is type II which is fraying of the superior glenoid labrum with detachment of the biceps anchor. Superior labrum anterior posterior (SLAP) lesions can also be associated with other shoulder pathology. Both MRI and MRA can be utilized in making the diagnosis with the coronal images being the most sensitive. The mechanism of injury can be either re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
10
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…Furthermore, no significant differences were found in preoperative symptoms or postoperative outcomes in analyzing results by patient age, a finding in contrast with several recent reports suggesting poorer outcomes after labral repair in older patient populations. 3,10,13,17,35 Postoperative outcomes were also not significantly different in patients presenting with pain alone and no instability. The current study had a 30% reported postoperative complication rate, compared with the 15% rate in Tokish et al This disparity may be the result of a broader definition of postoperative complications in the present report.…”
Section: Discussionmentioning
confidence: 83%
“…Furthermore, no significant differences were found in preoperative symptoms or postoperative outcomes in analyzing results by patient age, a finding in contrast with several recent reports suggesting poorer outcomes after labral repair in older patient populations. 3,10,13,17,35 Postoperative outcomes were also not significantly different in patients presenting with pain alone and no instability. The current study had a 30% reported postoperative complication rate, compared with the 15% rate in Tokish et al This disparity may be the result of a broader definition of postoperative complications in the present report.…”
Section: Discussionmentioning
confidence: 83%
“…8,10 Isolated SLAP lesions are believed to be relatively uncommon. In addition, when they occur with other concurrent shoulder pathology, SLAP lesions are unlikely to be the primary cause of pain or dysfunction.…”
mentioning
confidence: 99%
“…These injuries are often a result of either direct trauma to the shoulder or degeneration from chronic overuse. 21 Tears from chronic overuse are often encountered in overhead athletes and are proposed to be the result of either deceleration of the arm during the follow-through phase of throwing or the “peel-back mechanism” seen in the cocking phase in abduction and external rotation. 3,7 While conservative treatment may be effective in some patients, 11 if it fails, arthroscopic SLAP repair using suture anchor fixation is an effective treatment modality, yielding good results in young patients.…”
mentioning
confidence: 99%